One year of isometric exercise training for blood pressure management in men: a prospective randomized controlled study. Issue 12 (12th December 2022) - O'Driscoll, Jamie M.; Edwards, Jamie J.; Coleman, Damian A.; Taylor, Katrina A.; Sharma, Rajan; Wiles, Jonathan D.
Abstract : Objective: Isometric exercise training (IET) over 4–12 weeks is an effective antihypertensive intervention. However, blood pressure (BP) reductions are reversible if exercise is not maintained. No work to date has investigated the long-term effects of IET on resting BP. Methods: We randomized 24 unmedicated patients with high-normal BP to a 1-year wall squat IET intervention or nonintervention control group. Resting BP and various clinically important haemodynamic variables, including heart rate (HR), stroke volume (SV), cardiac output (CO) and total peripheral resistance (TPR) were measured pre and post the 1-year study period. Results: One year of IET produced statistically significant reductions in resting systolic (-8.5 ± 5 mmHg, P < 0.001) and diastolic (-7.3 ± 5.8 mmHg, P < 0.001) BP compared with the control group. There was also a significant reduction in resting HR (-4.2 ± 3.7 b/min, P = 0.009) and a significant increase in SV (11.2 ± 2.8 ml, P = 0.012), with no significant change in CO (0.12 ± 2.8 l/min, P = 0.7). TPR significantly decreased following IET (-246 ± 88 dyne·s/cm 5, P = 0.011). Adherence to the IET sessions was 77% across all participants (3x IET sessions per week), with no participant withdrawals. Conclusion: This novel study supports IET as an effective long-term strategy for the management of resting BP, producing clinically important, chronic BP adaptations in patients at risk of hypertension. Importantly, this work also demonstrates impressive long-term adherence rates, further supporting the implementation of IET as a means of effective BP management in clinical populations.